2021
DOI: 10.1108/jic-08-2020-0276
|View full text |Cite
|
Sign up to set email alerts
|

The cubic S-curve relationship between board independence and intellectual capital efficiency: does firm size matter?

Abstract: PurposeFirst, this study assesses firms’ efficiency of transforming intellectual capital (IC) components into firm performance. Second, this study examines (1) cubic S-curve relationship between board independence and IC efficiency and (2) how firm size moderates the cubic S-curve relationship.Design/methodology/approachThis study employs a stochastic nonparametric envelopment of data (StoNED) framework to estimate IC efficiency, which is derived from the estimation process of transforming structural, relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
(150 reference statements)
1
4
0
Order By: Relevance
“…Board independence acts as a resource from external IBs who have experience in managing IC; it thus has the potential to improve IC management to achieve higher efficiency, which, in turn, improves IB performance. This finding is consistent with (Kweh et al , 2021), who found that board independence will increase IC efficiency (Table 4).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Board independence acts as a resource from external IBs who have experience in managing IC; it thus has the potential to improve IC management to achieve higher efficiency, which, in turn, improves IB performance. This finding is consistent with (Kweh et al , 2021), who found that board independence will increase IC efficiency (Table 4).…”
Section: Resultssupporting
confidence: 92%
“…Although this finding rejects the assumptions of the resource-based theory, it is consistent with previous findings (Alsartawi, 2019; Rashid, 2018). An independent board moderated the significant positive relationship between IC and IB performance (0.071), suggesting that it is an effective monitor in the governance mechanism (Kweh et al , 2021). The optimal percentage of independent boards can increase the benefits of IC efficiency to have a positive impact on IB performance.…”
Section: Resultsmentioning
confidence: 99%
“…Nonaka et al (2017) argue that companies need to create new knowledge to ensure their future existence, so they must have good strategic and resource management. Several previous studies analyse the IC components independently of their dependent variables, such as research (Akkas and Asutay 2022;Chatterjee et al 2022;Dalwai and Mohammadi 2020;Dalwai and Salehi 2021;Kweh et al 2021;Vo and Tran 2021). This opinion considers each component's specific impact on performance rather than the impact of IC more broadly.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Due to the sustainability goal of firms amidst increasing competition, corporate drivers are becoming more enlightened on the need to develop their intellectual capital or assets (Buallay et al, 2020;Kweh et al, 2021). Intellectual capital improves and sustains rare and imitable comparative advantages (Sardo and Serrasqueiro, 2019;Xu et al, 2021;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of intellectual capital to firm performance, the complexity in measuring its efficiency becomes elusive. Ratio analysis is one of the most exhaustive measures of intellectual capital efficiency adopted in the literature (Anifowose et al, 2018;Isola et al, 2020;Kweh et al, 2021). The ratio analysis measure of intellectual capital uses the ratio of human, structural and relational intellectual capital to the firms' value-added.…”
Section: Introductionmentioning
confidence: 99%